The Influence of Liquidity, Profitability, Company Growth and Capital Structure on Company Value - Hertina, Dede (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
This research aims to determine the influence of liquidity, profitability, company growth and capital structure on company value. This research was conducted on consumer goods sector companies listed on the Indonesia Stock Exchange 2017-2022). The type of research used in this research is explanatory with a quantitative approach. The research results simultaneously state that Profitability, Liquidity, Company Growth and Capital Structure influence Company Value in Consumer Goods Industry companies listed on the Indonesian Stock Exchange for the period 2017 - 2019. Meanwhile, partial research results state that Liquidity has a significant negative effect on Company Value, profitability has a significant positive effect on Company Value, Company growth has no effect on Company Value and Capital Structure has no effect on Company Value in Consumer Goods Industry companies listed on the Indonesia Stock Exchange for the period 2017 – 2019. This can be seen based on the calculated t value of -1.068 which is smaller than the t table and the significance value is 0.289 so it can be seen that the value is above 0.05, that H4 which states that Capital Structure has an effect on Company Value is rejected.